Paternal lineages in southern Iberia provide time frames for gene flow from mainland Europe and the Mediterranean world - Candela L. Hernández; Jean-Michel Dugoujon; Luis J. Sánchez-Martínez; Pedro Cuesta; Andrea Novelletto; Rosario Calderón (Taylor & Francis Group, 2019)
Background: The geography of southern Iberia and an abundant archaeological record of human occupation are ideal conditions for a full understanding of scenarios of genetic history in the area. Recent advances in the phylogeography of Y-chromosome lineages offer the opportunity to set upper bounds for the appearance of different genetic components. Aim: To provide a global knowledge on the Y haplogroups observed in Andalusia with their Y microsatellite variation. Preferential attention is given to the vehement debate about the age, origin and expansion of R1b-M269 clade and sub-lineages. Subject and methods: Four hundred and fourteen male DNA samples from western and eastern autochthonous Andalusians were genotyped for a set of Y-SNPs and Y-STRs. Gene diversity, potential population genetic structures and coalescent times were assessed. Results: Most of the analysed samples belong to the European haplogroup R1b1a1a2-M269, whereas haplogroups E, J, I, G and T show lower frequencies. A phylogenetic dissection of the R1b-M269 was performed and younger time frames than those previously reported in the literature were obtained for its sub-lineages. Conclusion: The particular Andalusian R1b-M269 assemblage confirms the shallow topology of the clade. Moreover, the sharing of lineages with the rest of Europe indicates the impact in Iberia of an amount of pre-existing diversity, with the possible exception of R1b-DF27. Lineages such as J2-M172 and G-M201 highlight the importance of maritime travels of early farmers who reached the Iberian Peninsula.